2006
DOI: 10.1080/02687030500474922
|View full text |Cite
|
Sign up to set email alerts
|

The training of verb production in Broca's aphasia: A multiple‐baseline across‐behaviours study

Abstract: Background: Verb production is often impaired in Broca's aphasia: Action naming is more affected than object naming and in spontaneous speech the number and/or diversity of lexical verbs is low. Because verbs play a pivotal role in the sentence, these verb problems have a serious impact on the communicative contents of speech in daily life. Aims: The purpose of this study was to increase the informational content of spontaneous speech in two individuals with Broca's aphasia by training them in verb production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 22 publications
(24 reference statements)
0
46
0
Order By: Relevance
“…Although it has been shown that language training may generalize to linguistically related, but untrained items (Thompson, 2008), and according to some studies even to communicative settings (Bastiaanse, Hurkmans, & Links, 2006), treatment effects are usually larger for trained than for untrained items. In a meta-analysis of word finding therapy studies, Wisenburn and Mahoney (2009) calculated large effect sizes for trained words, but only minor gains for untrained, unexposed words.…”
Section: Computer Technology and The Disorder-oriented Treatment Apprmentioning
confidence: 99%
“…Although it has been shown that language training may generalize to linguistically related, but untrained items (Thompson, 2008), and according to some studies even to communicative settings (Bastiaanse, Hurkmans, & Links, 2006), treatment effects are usually larger for trained than for untrained items. In a meta-analysis of word finding therapy studies, Wisenburn and Mahoney (2009) calculated large effect sizes for trained words, but only minor gains for untrained, unexposed words.…”
Section: Computer Technology and The Disorder-oriented Treatment Apprmentioning
confidence: 99%
“…Overall, improvements were observed for trained verbs, but there was limited improvement to single-word retrieval of untrained verbs (Links et al, 2010;Raymer & Kohen, 2006). Some improvements to sentence production were reported (Bastiaanse et al, 2006;Edwards & Tucker, 2006;Links et al, 2010;McCann & Doleman, 2011), with improvement to connected speech in a few participants (Bastiaanse et al, 2006;Edwards & Tucker, 2006;Links et al, 2010). Although the improvements to sentence production and connected speech are encouraging, the gains observed in these studies were primarily structural and/or grammatical (Webster & Whitworth, 2012), not lexical.…”
mentioning
confidence: 66%
“…A subset of these studies (as described by Webster & Whitworth, 2012) focused primarily on sentence structure, syntax, and/or morphosyntax (e.g., Bastiaanse, Hurkmans, & Links, 2006;Conroy, Sage, & Lambon Ralph, 2009;Edwards & Tucker, 2006;Links, Hurkmans, & Bastiaanse, 2010;McCann & Doleman, 2011;Raymer & Kohen, 2006). Trained tasks included sentence completion and production and sentence production cuing hierarchies.…”
mentioning
confidence: 99%
“…Units such as Mean Length of Utterance (MLU; Brown, 1973) have been used in examining children (Berman 1985(Berman , 1997Bishop & Adams, 1990) and individuals with aphasia (Baltaxe & Guthrie, 1987;Bastiaanse, Hurkmans & Links, 2006). However, different MLUs may be associated with different languages, depending on their morphological systems.…”
mentioning
confidence: 98%